The Local Wisdom Study of Luan And Teben Concept on Balinese Ethnic Houses (Case Study: Balinese Ethnic Houses in Denpasar, Bali) - Wijaya, I Kadek Merta (University of Merdeka Malang, 2020)
Sanga Mandala is a concept that divide the layout of lowland Balinese house into nine zones. The intersection of two main axes, the ritual axis and the natural axis, forms the concept of Sanga Mandala. These axes have two poles called hulu/luan (mountain direction) and teben (sea direction). Along with times, the realization of Sanga Mandala in the form of buildings and zoning underwent a transformation in response to the increase in household members, modern mindset of the citizen, and tendency to follow contemporary trends. Changes to the zoning system that still follow the rules of traditional Balinese architecture are zones of sacred and ritual functions. With the development of modern mindset of the citizen, we can find those phenomena in Denpasar. This study aimed at examining the meaning of luan and teben on Balinese ethnic house layout in Denpasar. There is an interesting phenomenon that relates to the meaning of luan and teben in contemporary life. This study used interpretative naturalistic research method by emphasizing the empirical aspects of sensual, ethical, emic, logical, and transcendental. The results showed that there was a pattern of meaning on luan and teben in the conception of zoning, transformation of spaces and buildings, orientation of the building mass, as well as producing a pattern of meaning in zoning and ritual functions as the most important part in the residential space layout of Balinese ethnic houses in the midst of the development of Denpasar.Â DOI:Â https://doi.org/10.26905/lw.v12i2.4276